Оцінка снекової продукції з використанням борошна червоної сочевиці - Черняков, Валентин Анатолійович; Мельник, Оксана Юріївна; Cherniakov, Valentyn; Melnyk, Oksana (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті наведено результати дослідження органолептичних властивостей снекової продукції на основі борошна червоної сочевиці та овочевої сировини. Метою роботи є встановлення впливу рецептурного складу на формування сенсорного профілю продукту. Наукова новизна полягає у застосуванні дескрипторного аналізу відповідно до ДСТУ ISO 13299:2016 для оцінювання органолептичних характеристик снеків із комбінованої рослинної сировини та визначенні закономірностей їх зміни залежно від вмісту сочевичного борошна. Проведено оцінювання трьох дослідних зразків із вмістом борошна 26 %, 33 % та 40 %. Встановлено, що збільшення його частки до 33 % сприяє покращенню текстури, смаку та загальної гармонійності продукту, тоді як подальше підвищення призводить до погіршення окремих показників. Практична цінність полягає у визначенні оптимального рецептурного складу для забезпечення високої споживчої цінності снекової продукції. /// EN: The article presents the results of a study on the organoleptic properties of snack products developed on the basis of red lentil flour and vegetable raw materials. The relevance of the research is determined by the growing demand for snack products with improved nutritional value and balanced composition, as well as the need to replace traditional products with high fat and carbohydrate content by healthier alternatives of plant origin. The aim of the study was to determine the influence of formulation composition, in particular the content of red lentil flour, on the formation of sensory characteristics of snack products. The scientific novelty of the work lies in the application of descriptive analysis in accordance with DSTU ISO 13299:2016 for the evaluation of the sensory profile of snacks based on combined plant raw materials, as well as in identifying patterns of changes in organoleptic indicators depending on the proportion of lentil flour in the formulation. Three experimental samples containing 26 %, 33 % and 40 % of red lentil flour were investigated. Sensory evaluation was carried out using a descriptor-based approach, which included the assessment of appearance, color, aroma, taste and texture characteristics. The intensity of each descriptor was determined using a five-point scale, and the results were presented as mean values. Radar charts were used to visualize the sensory profiles of the samples. The results showed that increasing the proportion of lentil flour to a certain level contributes to the improvement of sensory characteristics, particularly crispness, color intensity and taste expression. However, further increase in its content leads to a decrease in taste harmony and optimal texture due to the formation of a denser and drier structure and a more pronounced legume flavor. It was established that the sample containing 33 % of red lentil flour demonstrated the most balanced sensory profile, characterized by high values of crispness, taste harmony and structural uniformity. This formulation ensures the highest level of consumer acceptability among the studied variants. The practical significance of the research lies in determining the optimal formulation parameters for the production of snack products based on plant raw materials, which can be used to improve existing technologies and develop new types of functional food products with enhanced sensory properties.
Evaluation of snack products using red lentil flour
Keywords: дескрипторний аналіз; сенсорний профіль; зернобобові культури; овочеві компоненти; рецептурний склад; споживча цінність; текстурні характеристики; descriptive analysis; sensory profile; legumes; vegetable components; formulation composition; consumer acceptability; textural characteristics